As intertextualidades pós-coloniais do estupro em Sorry, de Gail Jones - Sousa, Rafael Santos de (2020)
This thesis aims to analyse colonial violence, represented in the novel Sorry (2007), by the Australian writer Gail Jones, through a postcolonial perspective, that is, under an analytical view that seeks to revisit and comprehend the historical intertexts of colonization based not on the hegemonic position, but on the ones relegated to the social and geographical margins. This work is particularly centered on rapes commited by Nicholas Keene against his wife, Stella, and mainly to the ones he commits against the Aboriginal girls, Martha and Mary. Alongside such actions, other forms of violence perpetrated on indigenous people in Australia are hereby construed as the colonial rape, to wit, a set of sistematic violences applied against the tradicional population of a country invaded by imperialist ventures. At first, the colonial power discursive structures and the way the author metaphorizes and blurs them are observed through the construction of the characters and the narrative point of view. With this intention, valuable ideas of the postcolonial criticism were granted, such as: representativity and double subalternity, proposed by Gayatri Spivak; and in-betweenness and Third Space, articulated by Homi Bhabha. Forthwith, it is presented a discussion over the rape as an instrument of sistemic domination which can be identified under variable forms, but engenders in itself an urge to anihilate the other’s subjectivity and, foremost, over the representations of this act in the textual fabric, as suggested by Pierre Bourdieu and Lia Machado. Lastly, it is offered an analysis of aesthetic aspects of the novel, mainly, the ones concerned to the parodic and ironic references in Jone’s novel, based on the studies of postmodern narrative and intertextuality, presented by Linda Hutcheon and Tiphaine Samoyault. The Australian literary work analysed here recovers excerpts by William Shakespeare and the debate concerned to the Sorry Day, oficial date on which the Australian population celebrates the acknowledgement and apologizing for the oppression suffered by Aboriginal people. Thence, it is here supported the assumption about the author’s reinforcement of her commitment with a postmodern aesthetics of colonial past re-reading through the representation of rape, silence and the oppression of feminine characters in her novel.